Mental Health Outcomes for Adolescents with a History of Developmental Language Disorder: An Exploration of Risk Factors - Kilpatrick, Tina (Curtin University, 2020)
This research investigated mental health outcomes for adolescents with and without a history of Developmental Language Disorder (DLD), which affects approximately seven percent of the population, and is characterised by persistent difficulties in understanding and expressing language. The findings indicated that language difficulties and bullying victimisation worked together to increase emotional problems. These findings reinforce the importance of monitoring psychosocial wellbeing and vulnerability to bullying victimisation for adolescents with DLD.